1992
DOI: 10.3109/02713689209033480
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome oxidase activity in rat retina after exposure to 404 nm blue light*

Abstract: Cytochrome oxidase (CYO), a key enzyme in the respiratory chain, was observed as an indicator of retinal metabolism after an in vivo blue light exposure. Thirty Sprague-Dawley rats were exposed to optic radiation of 404 nm with a retinal dose of 110kJ/m2. Immediately after exposure, the CYO activity in the pigment epithelium, in the outer and inner segments of photoreceptors, and in the outer plexiform layer of the exposed retina, was reduced to one-third-to-half of the control level. However, there was an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…Different explanations have been given for blue light toxicity: (1) damage to blue-sensitive chromophores [3];…”
Section: Discussionmentioning
confidence: 99%
“…Different explanations have been given for blue light toxicity: (1) damage to blue-sensitive chromophores [3];…”
Section: Discussionmentioning
confidence: 99%
“…Numerous publications have since described the morphological changes in retinal pigment epithelium (RPE) induced by exposure to light [2,10,17,18,22,27,33]. Hansson cited the time course and oxidative enzyme changes in the retina [16,18] as the evidence that the primary site damaged was the RPE and that damage to the photoreceptor was only secondary.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed a variety of studies have suggested that photosynthesizers located to mitochondria generate ROS as a result of interaction with light [44][45][46][47][48][49][50][51]. Good evidence for this being the case was obtained by studies where freshly isolated mitochondria from the rat liver was exposed to light (400-760 nm) as impinging on the retina.…”
Section: Light Affects On Mitochondrial Photosynthesizersmentioning
confidence: 95%